2013
DOI: 10.3390/nu5093589
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Different Multivitamin Mineral Preparations with and without Guaraná on Mood, Cognitive Performance and Functional Brain Activation

Abstract: Previous work has identified the positive effects of the acute administration of a multivitamin-guaraná preparation during an effortful executive/working memory task. Here, we aimed to differentiate the effects of multivitamins with and without guaraná and to examine the neural substrates of such effects using functional magnetic resonance imaging (fMRI). Following a double-blind, placebo-controlled, randomised, balanced crossover design, 20 participants (mean age 29 ± 5.54 years) consumed multivitamin prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 41 publications
(57 reference statements)
6
39
0
Order By: Relevance
“…Guarana may improve working memory and cognitive performance in humans and animal models [80][81][82]. However, research data on this topic are controversial because other studies reported negative effects of energy drinks on executive functions in early adolescents [83].…”
Section: Discussionmentioning
confidence: 98%
“…Guarana may improve working memory and cognitive performance in humans and animal models [80][81][82]. However, research data on this topic are controversial because other studies reported negative effects of energy drinks on executive functions in early adolescents [83].…”
Section: Discussionmentioning
confidence: 98%
“…Previously, mood benefits of an acute multivitamin dose have only been identified for supplements containing the plant extract guarana, and not for standard multivitamin preparations Kennedy et al 2008;Scholey et al 2013). Due to the small number of studies in this area, it is not certain whether these mood effects can be solely attributed to the caffeine content of the guarana extract.…”
Section: Introductionmentioning
confidence: 97%
“…Secondary results from a 4-week randomised controlled trial are reported from the acute testing session 1-2 h following the administration of a single MVMH supplement or placebo. Mood measures were selected which have previously demonstrated sensitivity to multivitamin supplementation over longer time durations (Harris et al 2011;Long and Benton 2013;Pipingas et al 2013). Mood ratings were assessed at 1 h post dose and again at 2 h post dose after participants had completed an effortful cognitive battery.…”
Section: Introductionmentioning
confidence: 99%
“…Work from our laboratory has provided preliminary evidence of neurophysiological changes associated with MVM supplementation, exploring both acute doses and longer term supplementation using fMRI and Steady State Visual Evoked Potentials (SSVEP) – an electrophysiological technique with high temporal resolution (see below). In a pilot investigation of the acute effects of two MVM treatments, with or without guaraná, fMRI during completion of Rapid Visual Information Processing (RVIP) and Inspection Time tasks revealed increased blood oxygen level dependent (BOLD) response to active tasks for both MVM treatments compared to placebo (Scholey et al, 2013). This study also reported cognitive performance and mood benefits restricted to the MVM plus guaraná treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The pilot fMRI findings of Scholey et al (2013) studying acute effects of MVM administration were extended using SSVEP recordings during completion of the A-X Continuous Performance Task (A-X CPT; White et al, 2016). This study found distinct changes in SSVEP response during the A-X CPT associated with MVM supplementation containing higher B vitamin and mineral doses and a second MVM with lower micronutrient doses but additional guaraná.…”
Section: Introductionmentioning
confidence: 99%